POSTULAT PRZENIESIENIA AMERYKAŃSKIEJ KONCEPCJI „PLANU WYCHOWAWCZEGO” ROZWODZĄCYCH SIĘ RODZICÓW NA GRUNT PRAWA POLSKIEGO - Stojanowska, Wanda (Zeszyty Prawnicze, 2017)
The Postulate for Importing an American Concept of the „Upbringing Plan” of the Divorcing Parent into the Polish Family Law Summary The article presents the way in which the „upbringing plan” of divorcing parents functions in the United States on the example of its application in the states of Washington and Michigan. The American legislator created conditions for realization of the idea of a mutual performance of the parental authority by divorced parents among other things by means of a detailed regulation on the manner of preparation of such a plan according to a „Questionnaire” designed for this aim. This „upbringing plan” is to fulfil in particular four functions: a) to simplify parent’s regulation of the situation after the divorce; b) normative function; c) educational function; d) preventive function. The author critically analysis the provisions of the family and custodian code regulating the forms of the determinations regarding the parental authority in the divorce verdict and she compares them with American provisions on the „upbringing plan”. On these basis she concludes that first the plan is a perfect concept from both the legal and psychological perspective aiming at protecting the child’s good and second it ideally suits Polish divorce law, both de lege lata and de lege ferendoj It is, however, important in what manner the change of law will be performed. This kind of interception of a modern legislative solution provided for in America in the author’s view would definitely eliminate problems connected with the performance of the parental authority by divorced parents.